Clinical and Histologic Overlap and Distinction Among Various Hamartomatous Polyposis Syndromes. Issue 5 (22nd May 2019) - Gilad, Ophir; Rosner, Guy; Fliss-Isakov, Naomi; Aharon-Kaspi, Sivan; Strul, Hana; Gluck, Nathan; Kariv, Revital
Abstract : INTRODUCTION: Hamartomatous polyposis syndromes (HPS) are rare autosomal-dominant inherited disorders associated with gastrointestinal (GI) tract and other cancers. HPS include Peutz-Jeghers syndrome (PJS), juvenile polyposis syndrome (JPS), and phosphatase and tensin homolog hamartomatous tumor syndromes (PHTS). Diagnosis, management, and outcome prediction of HPS pose a clinical challenge. To characterize genotype, phenotype, histology and outcomes of individuals with HPS. METHODS: A retrospective cohort study (2004–2017) of consecutive patients that were clinically diagnosed with HPS that visited a specialized GI oncology clinic. Demographic, clinicopathological, and genetic data were obtained from medical records. RESULTS: Fifty-two individuals from 34 families were included. Common clinical manifestations were GI bleeding (40% JPS, 23% PJS, and 25% PHTS) and bowel obstruction (46.15% PJS and 11.4% JPS). Twenty patients (38.4%) underwent surgery, 5 of whom required multiple procedures. Higher polyp burden was associated with the need for surgery ( P = 0.007). Polyp histology varied widely with 69.2% of patients exhibiting histology different from the syndrome hallmark. GI cancer history was positive in 65%, 40%, and 50% of JPS, PJS, and PHTS families, respectively. Five (9.6%) patients developed cancers (one patient each had small bowel-1, colon-1, and thyroid-1, one patient had both small bowel adenocarcinoma and breast cancer, and one had both breast cancer and liposarcoma). Twenty (38.4%) patients tested positive for STK11, PTEN, SMAD4, BMPR1A, or AKT1 mutations: Sanger sequencing and multi-gene next generation sequencing panels detected mutations in 40.9% and 100% of tested cases, respectively. DISCUSSION: HPS patients present versatile phenotypes with overlapping clinical and histological characteristics. Polyp burden is associated with the need for surgery. Next-generation sequencing increases mutation detection.